2019
DOI: 10.3390/land8040064
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Development of Riparian Ranchlands Using Ecosystem Services at the Aravaipa Watershed, SE Arizona

Abstract: This paper describes how subdivision and development of rangelands within a remote and celebrated semi-arid watershed near the US–Mexico border might affect multiple ecohydrological services provided, such as recharge of the aquifer, water and sediment yield, water quality, flow rates and downstream cultural and natural resources. Specifically, we apply an uncalibrated watershed model and land-change forecasting scenario to consider the potential effects of converting rangelands to housing developments and doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…84 Finally, studies have demonstrated that watershed models can be used for predictive-framework and decision-support. 25,69,70,76,80,87 These advances in restoration science, with science-based evidence that dispels prior assumptions, are being acknowledged by partner agencies who can revise management strategies 53,88 to help bridge the disconnect between restoration practice and the value of surface-water availability.…”
Section: Resultsmentioning
confidence: 99%
“…84 Finally, studies have demonstrated that watershed models can be used for predictive-framework and decision-support. 25,69,70,76,80,87 These advances in restoration science, with science-based evidence that dispels prior assumptions, are being acknowledged by partner agencies who can revise management strategies 53,88 to help bridge the disconnect between restoration practice and the value of surface-water availability.…”
Section: Resultsmentioning
confidence: 99%
“…Established partnerships offered the perfect "field laboratory" at the Babocomari Ranch, where the Walton Family Foundation provided funding to SIRC partners (Borderlands Restoration Network [BRN], USGS, Lacher Hydrological Consulting, and Watershed Management Group) to study and model surfaceto-groundwater relations pertaining to gabion installation (Figure 3B). 28,29 The SIRC partners recognize the value of upcoming generations and have invested together to create strong foundations to support them. The SIRC has a growing pool of subscribers and volunteers that can now orchestrate a multidisciplinary agenda across a watershed, teaching practices to improve the health of watersheds and benefits to local communities.…”
Section: Improving the Enabling Environmentmentioning
confidence: 99%
“…The quantification of water volumes in these cycles supports understanding of how humans can impact water availability and manage water resources across local, regional, and national scales. For example, effectively quantifying these cycles can inform sustainable management of agricultural water resources [1][2][3], water use and availability associated with changes in land use/land cover and restoration [4][5][6], and general water resources management for decision-making [7,8]. In the case of water storage (i.e., surface water, ground water) and surface water flows, vast ground-based networks exist to accurately measure these dynamics, including the U.S. Geological Survey (USGS) National Water Information System (NWIS) (i.e., surface water discharge, storage, groundwater) [9,10].…”
Section: Introduction 1evapotranspiration and The Water Budgetmentioning
confidence: 99%